REVISIT INTENTION (RI) OF TOURISTS: A STUDY OF YOUNG BEACH-GOERS IN GOA, INDIA - Kumar B, Pradeep (Revista de turism - studii și cercetări în turism, 2023)
It is evident that inducing visitors to revisit the tourist destinations and resorts, where they stay, is an important way of smoothening out revenue generation for tourism firms rather than attracting new tourists using costly advertisement and marketing strategies. This revelation has paved the way for an array of Revisit Intention studies in the field of tourism. Many such studies regard the revisit intention (RI) of tourists as a binary variable that is with two outcomes viz—yes, having to revisit intention or No. Distinct from this, this study enquires into the revisit intention by categorizing this into three: Tourists with High Revisit Intention (HRI), Moderate Revisit Intention (MRI), and No Revisit Intention (NRI). Drawing on data collected from 120 College going students visiting Goa Beaches, the study reveals that most tourists have a revisit intention. Apart from this, the study also proves that the revisit intention of tourist is dependent on factors like cleanliness and unpolluted nature of the beaches, service quality of the staff in resorts, and the quality of accommodation, safety, and security (SnS) of beaches and resorts, and finally, the feeling of a consumers’ surplus (Visitors’ Surplus).